Scoring model to predict early-onset bacterial sepsis at Dr. Mohammad Hoesin Hospital, Palembang - Lilik Fitriana; Afifa Ramadanti; Indrayady Indrayady (Indonesian Pediatric Society, 2023)
Background Early-onset bacterial neonatal sepsis (bacterial EONS) is one of the most common causes of death and illness in newborns. Assessment of risk factors is important to identify infants who are more susceptible to bacterial EONS. A scoring model based on maternal and infant risk factors would be useful for predicting bacterial EONS. Objective To develop a scoring model to predict bacterial EONS by examining maternal and neonatal risk factors. Methods This diagnostic test study was conducted at Mohammad Hoesin Hospital, Palembang between January-September 2021 using various maternal and infant risk factors. Subjects were newborns suspected of having early-onset bacterial sepsis with birth weight >1000 grams. The potential risk factors evaluated consisted of premature rupture of membranes >18 hours, greenish-thick-and-foul-smelling amniotic fluid, maternal body temperature >38Â°C, maternal leukocytosis >15.000/?L, gestational of <37 weeks, birth weight of <2500 grams, and APGAR score of <7 at 1 minute. One hundred sixty-two subjects were selected consecutively. Analyses included odds ratio, logistic regression test, and ROC curve to assess sensitivity and specificity of each risk factor. Results Premature rupture of membranes >18 hours, greenish-thick-and-foul-smelling amniotic fluid, male sex, and gestation of <37 weeks were risk factors for bacterial EONS. In the multivariate analysis, premature rupture of membranes >18 hours had an OR of 5.94 (95%CI 1.69 to 20.86, P=0.005), greenish-thick-and-foul-smelling amniotic fluid had an OR of 3.74(95%CI 1.16 to 12.02, P=0,027), male sex had an OR of 4.28 (95%CI 1.14 to 16.02, P=0.031), and gestation of <37 weeks had an OR of 3.1 (95%CI 0.82 to 11.72, P=0.094). In the scoring model, each of these four risk factors were assigned a score of 2 (for maternal risk factors) and 1 (for neonatal risk factors). Using a cut-off score of 2.5 to predict bacterial EONS, the scoring system had a sensitivity of 80% and specificity of 47%. Conclusion Our scoring model of maternal and infant risk factors can be used to screen for possible bacterial EONS at an earlier stage of illness, although with limited specificity.